Observationally Constrained Cloud Phase Unmasks Orbitally Driven Climate Feedbacks. Issue 6 (25th March 2021) - Sagoo, Navjit; Storelvmo, Trude; Hahn, Lily; Tan, Ivy; Danco, James; Raney, Bryan; Broccoli, Anthony J.
Abstract: The mechanisms which amplify orbitally driven changes in insolation and drive the glacial cycles of the past 2.6 million years, the Pleistocene, are poorly understood. Previous studies indicate that cloud phase feedbacks oppose ice sheet initiation when orbital configuration supports ice sheet growth. Cloud phase was observationally constrained in a recent study and provides evidence for a weaker negative cloud feedback in response to carbon dioxide doubling. We observationally constrain cloud phase in the Community Earth System Model and explore how changes in orbital configuration impact the climate response. Constraining cloud phase weakens the negative high latitude cloud phase feedback and unmasks positive water vapor and cloud feedbacks (amount and optical depth) that extend cooling to lower latitudes. Snowfall accumulation and ablation metrics also support ice sheet expansion as seen in proxy records. This indicates that well‐known cloud and water vapor feedbacks are the mechanisms amplifying orbital climate forcing. Plain Language Summary: The recent ice ages represent large transitions in climate that are forced by small changes in solar radiation, driven by variations in the Earth's orbit. This study aims to identify plausible mechanisms that can amplify this small solar signal and lead to the development of large ice sheets, thereby improving our understanding of the climate system. Cloud phase (the proportion of liquid to ice) is poorly represented in climate models and previous work has shown that this can lead to an underestimation of the climate response to carbon dioxide forcing. This study explores the climate response to orbital forcing when cloud phase is observationally constrained by satellite. Previous modeling studies have found that when high latitude solar radiation is reduced due to orbital variations, clouds thin, allowing more absorption of solar radiation which effectively opposes the orbital cooling that encourages ice sheet growth. We find that when cloud phase is constrained, this opposing cloud thinning is reduced and cooling extends to lower latitudes via cloud and water vapor feedbacks. Our work indicates that well‐understood climate processes are the mechanisms that amplify orbital climate forcing, and reiterate the importance in properly simulating cloud phase in climate models. Key Points: Low cloud phase feedback is less negative in response to orbital forcing when cloud phase is observationally constrained by satellite data Shortwave cloud and net water vapor feedbacks are identified as mechanisms which amplify orbitally driven changes in insolation Improving cloud phase representation in models is important for understanding the climate system response to forcing in past climates